The ECB's Fiscal Policy - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2018)
While the ECB helped mitigate the euro crisis in the aftermath of Lehman, it has stretched its monetary mandate and moved into fiscal territory. This text describes and summarises the crucial role played by the ECB in the intervention spiral resulting from its bid to manage the crisis. It also outlines ongoing competitiveness problems in southern Europe, discusses the so-called austerity policy of the Troika, comments on QE and presents two alternative paths for the future development of Europe.
Keywords: E02; E50; E52; E58; H50; H60; H63; 330